PENGARUH ADIKSI GAWAI TERHADAP PRESTASI BELAJAR MAHASISWA PRODI DIPLOMA III AKADEMI FARMASI YARSI PONTIANAK - Fadli Fadli; Kharisma Justicia; aulia azanita (Politeknik Meta Industri, 2021)
Gawai addiction is addiction to gadgets so that it spends more time using gadgets. Gawai addiction can have an impact on learning achievement. This study aims to determine the effect and how far the level of gadget addiction is on the learning achievement of students in Diploma III of Akademi Farmasi Yarsi Pontianak. The population in this study were students of the Akademi Farmasi Yarsi Pontianak batch of 2019. The sample collection technique used was simple random sampling with 30 respondents. This research method is a survey method with the type of observational analytic research using a questionnaire. The analysis technique in this study uses the t test to test the research hypothesis and to see the effect of the relationship between the independent variable (gadget addiction) and the dependent variable (learning achievement), a simple linear regression test is used. The results obtained a significance value of 0.029 <0.05, it can be concluded that there is an influence on the relationship between device addiction and learning achievement and the t count value is 2.307> 2.048, so it can be concluded that the hypothesis in this study is accepted and the effect of the independent variable (gadget addiction) on the variable bound (Learning Achievement) amounted to 16.0%. The conclusion of this study is that there is a significant negative relationship between device addiction and student achievement of the Diploma III Akademi Farmasi Yarsi Pontianak.Keywords : Addiction, Gawai, Learning Achievement